Application of multiple regression models for inflation modelling - Čuvak, Ana; Kalinauskas, Žilvinas (Lietuvos matematikos rinkinys, 2021)
This paper examines the Lithuanian consumer price inflation from 1996 January till 2006 December using a modern non-stationary time series and econometric theory.  The multiple regressionmodels are proposed for inflation modeling. The stationarity of Lithuanian inflation and the main explored exogenous variables are analyzed using the augmented Dickey–Fuller test.  All indicators are integrated of order one.  Vector error correction (VECM) model of Lithuanian inflation processes is investigated and proposed for inflation modeling.
Keywords: consumer price inflation; HCPI; vector error correction model; cointegration